Retaining early career registered nurses: a case study. Issue 1 (December 2016) - Mills, Jane; Chamberlain-Salaun, Jennifer; Harrison, Helena; Yates, Karen; O'Shea, Andrea
Abstract Background A core objective of the Australian health system is to provide high quality, safe health care that meets the needs of all Australians. To achieve this, an adequate and effective workforce must support the delivery of care. With rapidly changing health care systems and consumer demographics, demand for care is increasing and retention of sufficient numbers of skilled staff is now a critical priority to meet current and future health care demands. Nurses are the largest cohort of professionals within the health workforce. Reducing the rates at which nurses leave the profession and supporting nurses to practice in their profession longer will have beneficial implications for the sustainability of a nursing workforce and, ultimately, to patient outcomes. The aim of the study was to describe and explain early career registered nurses' (ECRNs) experiences and support requirements during the first five years of practice for the purposes of identifying strategies that would support greater retention of ECRNs. Methods A single case study design focused on early career registered nurses (ECRNs) working in a hospital and health service in northern Australia. The research team adopted Djukic et al's definition of ECRNs as "RNs who have practiced for less than 5 years". Data was collected via three individual interviews and two focus groups. Thirty-five ECRNs participated in the study. Results Qualitative analysis of data generated during interviews and focus groups, identified the key themes ofreceiving career advice andchoice or no choice . Analysis of study data in the context of the broader literature resulted in the researchers identifying six areas of focus for ECRN retention: 1) well-planned, supported and structured transition periods; 2) consideration of rotation through different areas with a six month minimum for skills development; 3) empowering decision making; 4) placement opportunities and choice in decisions of where to work; 5) career advice and support that considers ECRNs' personalities and skills; and 6) encouragement to reflect on career choices. Conclusions Reducing turnover and improving retention relies on understanding the factors that influence nurses' decisions to leave or remain within an organisation and the profession. Ensuring nurses in the current workforce remain engaged and productive, rather than leave the profession, is reliant on addressing factors that cause attrition and implementing strategies that strengthen retention rates and workforce sustainability.